Cohort consequences of drought and family disruption for male and female African elephants. (24th December 2021) - Lee, Phyllis C; Moss, Cynthia J; Njiraini, Norah; Poole, Joyce H; Sayialel, Katito; Fishlock, Vicki L
Abstract: Cohort effects, reflecting early adversity or advantage, have persisting consequences for growth, reproductive onset, longevity, and lifetime reproductive success. In species with prolonged life histories, cohort effects may establish variation in age-sex structures, while social structure may buffer individuals against early adversity. Using periods of significant ecological adversity, we examined cohort effects for male and female elephants ( Loxodonta africana ) over almost 50 years in Amboseli, Kenya. Mortality spiked during severe droughts with highest mortality among calves under 2 years and females over 40 years. Deaths of oldest females resulted in social disruption via matriarch turnover, with potential impacts on resource acquisition for survivors. We predicted that survivors of high mortality and social challenges would have altered life-history trajectories, with later age at first reproduction and reduced age-specific fertility for females and slow transitions to independence and late-onset of potential mating or musth among males. Contrary to expectations, there were no persisting early drought effects on female age at first conception while matriarch loss around puberty accelerated reproductive onset. Experience of an early life drought did not influence age-specific reproductive rates once females commenced reproduction. Males who survived an early drought exhibited complex consequences: male age at family independence was later with larger peer cohort size, but earlier with drought in year of independence (13.9 vs 14.6 years). Early drought had no effect on age at first musth, but male reproductive onset was weakly associated with the number of peers (negative) and age at independence (positive). Abstract : Do early-life disadvantages mean shorter, less successful lives, or can those disadvantages be overcome if later life is good or includes strong social support? For African elephants, whose long lives and strong bonds might buffer early hardship, experiencing environmental adversity in early life reduces longevity, as does losing a mother post-weaning or a family matriarch. While surviving females experience few long-term effects on their reproduction, we find complex consequences for male dispersal and reproductive onset. Many peers accelerate male family departure but delay reproductive careers.